2018
DOI: 10.1097/md.0000000000011822
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different drug delivery methods for Endostar combined with a gemcitabine/cisplatin regimen in locally advanced or metastatic lung squamous cell carcinoma

Abstract: Continuous endovenous administration of Endostar (CE) gradually replaced drip intravenous administration of Endostar (DE) in lung squamous cell carcinoma (SCC) treatment presently, but the efficacy and safety of CE and DE which is better in advanced lung SCC are yet unclear. To evaluate the feasibility of CE as an alternative to DE with gemcitabine/cisplatin (GP) chemotherapy. Data were collected from patients admitted with locally advanced or metastatic lung SCC from January 2011 to April 2015, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…In the report by Li et al 18 advanced NSCLC treated with CIV Endostar combined with chemotherapy showed a significantly higher disease control rate (86.2% vs. 70.7%, P < 0.01), longer median PFS (six months vs. four months, P = 0.037) and median OS (17.5 months vs. 13.5 months, P = 0.034) compared with IV Endostar combined with chemotherapy. The trend seen in the single-center retrospective study by Cheng et al19 was similar to that in the report by Li et al Yao et al 20 retrospectively compared the efficacy of CIV Endostar to IV Endostar in advanced or metastatic lung squamous cell carcinoma, both combined with gemcitabine/cisplatin chemotherapy (GP regimen). The median OS in the CIV group appeared to be longer compared with the IV group (22.9 months vs. 14.3 months).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the report by Li et al 18 advanced NSCLC treated with CIV Endostar combined with chemotherapy showed a significantly higher disease control rate (86.2% vs. 70.7%, P < 0.01), longer median PFS (six months vs. four months, P = 0.037) and median OS (17.5 months vs. 13.5 months, P = 0.034) compared with IV Endostar combined with chemotherapy. The trend seen in the single-center retrospective study by Cheng et al19 was similar to that in the report by Li et al Yao et al 20 retrospectively compared the efficacy of CIV Endostar to IV Endostar in advanced or metastatic lung squamous cell carcinoma, both combined with gemcitabine/cisplatin chemotherapy (GP regimen). The median OS in the CIV group appeared to be longer compared with the IV group (22.9 months vs. 14.3 months).…”
Section: Discussionsupporting
confidence: 55%
“…The trend seen in the single‐center retrospective study by Cheng et al .19 was similar to that in the report by Li et al . Yao et al . retrospectively compared the efficacy of CIV Endostar to IV Endostar in advanced or metastatic lung squamous cell carcinoma, both combined with gemcitabine/cisplatin chemotherapy (GP regimen).…”
Section: Discussionmentioning
confidence: 99%
“…Three thousand eight hundred thirty-one records were further excluded as they did not meet the inclusion criteria. Finally, nine studies were identified as eligible for inclusion in this systematic review, including four cohort studies [18][19][20][21] and two RCTs [22,23] and three NRCTs [24][25][26]. Table 1 showed the characteristics of included studies.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 597 advanced NSCLC participants were included (CIV: 300 and IIV: 297), with ages ranging from 24 to 78 years. The histological types of NSCLC included both SqCC and ADC in five studies [20][21][22][23][24], only SqCC in one study [18], and were unknown in three studies [19,25,26]. TNM staging of advanced NSCLC included both stage III and IV in six studies [18][19][20][22][23][24], only stage IV in one study [26], and were not reported in two studies [21,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation